Pengaruh Unggahan Konten Sales Promotion Instagram @Lashboss.Id terhadap Keputusan Pembelian Produk Lash Boss - Rahmananda, Naila; Yuni, Firdaus; Rifai, Maulana (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Naila Rahmananda, 1910631190184, 2023, The Influence of Sales Promotion Content Upload on @lashboss.id Instagram Account on Purchasing Decisions, Communication Studies Program, Singaperbangsa University Karawang.Currently, the development of the beauty industry in Indonesia has now begun to rampant and is growing very rapidly, one of which is in the field of skincare, especially eyelash serum. Through uploading sales promotion content carried out by Instagram @lashboss.id, it becomes the right combination in making purchasing decisions by @lashboss.id Instagram followers. The purpose of this study is how much influence the upload of sales promotion content on the @lashboss.id Instagram account has on purchasing decisions. In this study using the AISAS theory (Attention, Interest, Search, Action and Share) and the method used is quantitative method with descriptive research with sample withdrawal using simple random sampling with the number of respondents as many as 100 instagram followers @lashboss.id and the focus of this research is on instagram followers @lashboss.id who are female. Based on the research results obtained, Sales Promotion Content Upload has a significant effect on Purchasing Decisions with a value of 65.2%, the remaining 34.8% is influenced by other variables not examined.